Diabetic Retinopathy and Insulin Insufficiency: Beta Cell Replacement as a Strategy to Prevent Blindness - Ipp, Eli (Frontiers in Endocrinology, 2021)
Diabetic retinopathy (DR) is a potentially devastating complication of diabetes because it puts patients at risk of blindness. Diabetes is a common cause of blindness in the U.S. and worldwide and is dramatically increasing in global prevalence. Thus new approaches are needed to prevent this dreaded complication. There is extensive data that indicates beta cell secretory failure is a risk factor for DR, independent of its influence on glycemic control. This perspective article will provide evidence for insufficient endogenous insulin secretion as an important factor in the development of DR. The areas of evidence discussed are: (a) Presence of insulin receptors in the retina, (b) Clinical studies that show an association of beta cell insufficiency with DR, (c) Treatment with insulin in type 2 diabetes, a marker for endogenous insulin deficiency, is an independent risk factor for DR, (d) Recent clinical studies that link DR with an insulin deficient form of type 2 diabetes, and (e) Beta cell replacement studies that demonstrate endogenous insulin prevents progression of DR. The cumulative data drive our conclusion that beta cell replacement will have an important role in preventing DR and/or mitigating its severity in both type 1 diabetes and insulinopenic type 2 diabetes.